2018
DOI: 10.1029/2018gl077388
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Gravity Waves in the Ionosphere and Thermosphere During the 2017 Solar Eclipse

Abstract: As a cavity of solar radiation created by the lunar shadow moves across the United States on 21 August 2017, decreases in local ionospheric and thermospheric (IT) temperature and density are anticipated. The average velocity of the total solar eclipse across the United States is ~700 m/s. The supersonically moving lunar shadow has induced bow waves and gravity waves that are observed by the Global Navigation Satellite System (GNSS) network. We use the Global Ionosphere‐Thermosphere Model, a global circulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 30 publications
10
43
0
1
Order By: Relevance
“…Their results showed TIDs with a dominant peak at about 20–30 min and broadly extended to 20–90 min periods, without details about the wavelength of the observed TIDs. A simulation of bow waves during the eclipse (Lin et al, ) reproduced TIDs with a period of 20–30 min and therefore similar characteristics to the bow waves observed by (Zhang et al, ). They also fall within the range of the dominant frequency peak of the TIDs observed by (Nayak & Yigit, ).…”
Section: Introductionsupporting
confidence: 72%
“…Their results showed TIDs with a dominant peak at about 20–30 min and broadly extended to 20–90 min periods, without details about the wavelength of the observed TIDs. A simulation of bow waves during the eclipse (Lin et al, ) reproduced TIDs with a period of 20–30 min and therefore similar characteristics to the bow waves observed by (Zhang et al, ). They also fall within the range of the dominant frequency peak of the TIDs observed by (Nayak & Yigit, ).…”
Section: Introductionsupporting
confidence: 72%
“…The similarities between the P03, P14, and P32 spectra cannot be explained by this interpretation. However, the three sets of spectra are consistent with the modeling works by Eckermann et al () and Lin et al (), which point to a TID wavefield setup by the eclipse umbra and penumbra.…”
Section: Discussionsupporting
confidence: 89%
“…The authors attributed the wave activity to the eclipse, noting that their results are consistent with Zhang et al () and that the wave activity can be generated by the eclipse of a uniform solar EUV disk. Although the GITM model is too coarse to resolve horizontal wavelengths smaller than 316 km and the variations detected by GAP‐O, the appearance of wave activity due to the eclipse in GITM is consistent with Zhang et al's () results (Lin et al, ) and with the GAP‐O measurements. Indeed, the present measurements would serve to motivate contemporary IT models to reproduce the scales of the observed disturbances for the August 2017 eclipse and to simulate those for future eclipses, such as the 2 July 2019 eclipse.…”
Section: Discussionsupporting
confidence: 88%
“…Besides geomagnetic storms, solar eclipses are also known to excite AGWs (e.g., Chimonas & Hines, ; Liu et al, ) that alter the IT system (Harding et al, ; Lin et al, ). Liu et al () conclude that the ionospheric perturbations that they observed using ionosondes during the total solar eclipse of 24 October 1995 were most likely due to plasma upflow and downflow induced by rapid temperature increase immediately following the eclipse.…”
Section: Introductionmentioning
confidence: 99%